Christian Fredrick Schwartz: his contributions to South India - Jeyaraj, Daniel (Lutheran Heritage Archives, Gurukul Lutheran Theological College and Research Institute, 1999)
Papers presented at a seminar conducted in Thanjavur from 26th-28th Feb. 1998.
English and Tamil - Includes bibliographical references - "Literature on C.F. Schwartz in South India": (p. [146]-150)
Keywords: Swartz, Christian Frederick